Safety of leucodepleted salvaged blood in oncological surgery: an in vitro model. Issue 8 (6th October 2017) - Marraccini, C.; Merolle, L.; Berni, P.; Boito, K.; Tamagnini, I.; Kuhn, E.; Ragazzi, M.; Baricchi, R.; Pertinhez, T. A.
Abstract : Intra‐operative blood cell salvage (IOCS) is mainly avoided in onco surgery due to the suspicion that it could increase metastasis' risk. We simulated IOCS followed by leucodepletion: HCT116 (human colorectal cancer) cells were inoculated into packed red blood cells units, and their distribution was evaluated, step‐by‐step, by flow cytometry and immunohistochemistry. Most of HCT116 cells were lost during washing, and almost completely removed after filtration. IOCS plus leucodepletion could be of great advantage for oncological patients, where allogenic blood transfusion could influence tumour progression.